2014
DOI: 10.2337/db14-1149
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 6 Expression and Inflammatory Activity in Diabetic Atherosclerotic Plaques: Effects of Incretin Treatment

Abstract: The role of sirtuin 6 (SIRT6) in atherosclerotic progression of diabetic patients is unknown. We evaluated SIRT6 expression and the effect of incretin-based therapies in carotid plaques of asymptomatic diabetic and nondiabetic patients. Plaques were obtained from 52 type 2 diabetic and 30 nondiabetic patients undergoing carotid endarterectomy. Twenty-two diabetic patients were treated with drugs that work on the incretin system, GLP-1 receptor agonists, and dipeptidyl peptidase-4 inhibitors for 26 6 8 months b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(135 citation statements)
references
References 37 publications
5
124
0
6
Order By: Relevance
“…In addition, a subanalysis of the Diabetes Control and Complications Trial/ Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) demonstrated that the relationships between serum biomarkers of chronic inflammation and endothelial injury at multiple time points and the progression of carotid IMT remain unclear in patients with type 1 diabetes (29). Interestingly, a recent report suggested that evaluation of local inflammation and oxidative stress in the vascular wall, not in serum, was helpful in the full assessment of "non-glycaemicdependent" antiatherosclerotic effects of DPP-4 inhibitors (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a subanalysis of the Diabetes Control and Complications Trial/ Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) demonstrated that the relationships between serum biomarkers of chronic inflammation and endothelial injury at multiple time points and the progression of carotid IMT remain unclear in patients with type 1 diabetes (29). Interestingly, a recent report suggested that evaluation of local inflammation and oxidative stress in the vascular wall, not in serum, was helpful in the full assessment of "non-glycaemicdependent" antiatherosclerotic effects of DPP-4 inhibitors (30).…”
Section: Discussionmentioning
confidence: 99%
“…#P , 0.01. §P , 0.001. subjects of the above-mentioned three trials (29)(30)(31) were patients with T2DM with a history of CVD or at high risk for CVD. In comparison, our study enrolled insulin-treated subjects with T2DM who were free from apparent CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt6 protein expression is downregulated in diabetic atherosclerotic lesions (38). A previous study identified that H 2 O 2 treatment results in marked reduction of Sirt6 in endothelial cells (39).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, the effect of incretin-based therapies on carotid plaques should be mentioned. The findings indicate on beneficial effects of GLP-1RA on morphological and compositional characteristics of a plaque phenotype through the sirtuin 6 pathway [7]. Further investigations will elucidate this relationship and show if such effects may translate into a reduction of CV events in T2DM subjects.…”
mentioning
confidence: 75%